PERAN GURU BK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS X SMA NEGERI 6 PONTIANAK - Aziz, Qithfirul; Astuti, Indri; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study contained the Role of Guidance and Counseling Teachers in Improving Student Learning Motivation. The problem in this study was how Â the role of the teacher and the counseling as: (1) Motivator (2) Director (3) Initiator (4) Falisitator (5) Mediators (6) Evaluator. The method used descriptive method and the form of research is survey. The population is 45 people. This study used a quantitative approach. The data collection technique while the data collection tool is a questionnaire. The results of the study showed the Role of Guidance and Counseling Teachers in Improving Learning Motivation for Class X Students in Pontianak State High School in the category